Adjust the frequency of routine maintenance aircraft maintenance considering the human factor - Бурлаков, В.І.; Пучков, Ю.П.; Попов, Д.В. (Proceedings of National Aviation University (archive), 2009)
Possibility of adjustment periodicity regulations works is examined at the use by strategy maintenance on the level of reliability aviation technics wares taking into account quality of lead through works by aviation personnel at aircraft maintenance.